EFFECT OF IRIS DEVELOPMENT ON SURVIVAL IN HIV-TB PATIENTS ON ANTIRETROVIRAL THERAPY AMONG NORTH INDIAN POPULATION - Gupta, Priyanka; Tripathi, Anil Kumar; Jain, Amita; Prasad, Rajendra; Singh, Kaleshwar Prasad; Vaish, Arvind Kumar; Misra, Rajendra Prasad (Indian Journal of Community Health, 2012)
Background: The survival of people with HIV-associated TB has not been extensively studied. The objective of this present study was to explore the association of Immune reconstitution inflammatory syndrome (IRIS) development and mortality in HIV patients initiated on antiretroviral therapy (ART). Methods: This was a prospective cohort study of 400 HIV positive patients who initiated antiretroviral therapy and followed up for one year. Baseline clinical and immunological parameters were assessed. Results: A total of 38 (9.5%, 95%CI=6.6-12.4) patients developed IRIS within one year of follow-up. The mean duration of development of IRIS was 2.87 months (95%CI=2.08-3.67). The mortality was almost two times significantly higher in those patients who developed IRIS (21.1%) as compared to those who did not develop (9.7%) (RR=2.18, 95%CI=1.09-4.35, p=0.03). The average survival was significantly lower in those patients who developed IRIS (10.43 months) as compared to those who did not developed IRIS (11.5 months) (Log rank test p=0.03). Conclusion: Appropriate use of ART to preserve immunity and treat HIV infection, ensuring high levels of coverage and compliance is required to prevent TB. The DOTS strategy is useful to ensure cure of TB in patients with HIV/AIDS. A strong coordination between the national TB and the AIDS control programs is required for effective management of HIV-TB patients.